Ace the ielts : - Braverman, Simone (Tổng hợp Thành phố Hồ Chí Minh, 2013)
This excellent self-study book for intense IELTS preparation in a few weeks is designed to help students achieve their best personal score. All the tips, techniques, strategies and advice are focused on maximizing students’ score by increasing their task-solving speed and efficiency, and preventing typical mistakes. 'Ace the IELTS' is loved by teachers as well as students.